E-Business in Health Care Systems - Hamid Reza Rezaian; Nilufar Mohammad Zadeh; Hossein Dargahi (Tehran University of Medical Sciences, 2012)
Background and Aim: The use of electronic operations in health care industry has many positive points such as health care quality improvement, reduction in costs, and increased efficiency. Besides talking about the concept of Mobile Commerce (M-Commerce) as well as its benefits and challenges, the present article presents suitable approaches to benefit more from this new technology in the field of health, especially in the private sector. Materials and Methods: This review article was performed based on a literature review and a search through such valid sites as Science Direct, Emerald, and Magiran, and also an advanced search in Google. In this paper, the researchers studied national and international documents about the application of communication and IT tools -- particularly mobile and wireless tools, E-commerce, and M-commerce -- from 1996 to 2011.Results: E-business can be considered as one of the subsets of E-Health, and M-commerce as one of the E-business models is a very useful tool in developing countries. With this tool, organizations located in remote places can have access to potential customers and gain valuble benefits. Efficient application of E-business models in Iran requires the identification of opportunities and barriers as well as the preparation of suitable and basic plans with regard to socio-economic factors together with the provision of executive, legal, technological, and communications infrastructures.